2022
DOI: 10.1039/d2ay00804a
|View full text |Cite
|
Sign up to set email alerts
|

An ion imprinted magnetic organosilica nanocomposite for the selective determination of traces of Cd(ii) in a minicolumn flow-through preconcentration system coupled with graphite furnace atomic absorption spectroscopy

Abstract: In this paper we present the determination of ultratraces of cadmium ions in water by means of a minicolumn (MC) flow-through preconcentration system coupled to graphite furnace atomic absorption spectrometry....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…The procedure shows suitable analytical characteristics with a LOD of 0.64 ng L −1 , a linear calibration range of 2.5-100 ng L −1 , and RSD of 1.9% (n = 6; 10 ng L −1 ) with lifetimes above 800 cycles. 153 The successful application of primary and secondary amines (PSA) allows us to extract by SPE the available Pb (II) in soil samples by neutral salt extraction within the best pH range of 3.0-8.0. 154 Amine-and thiol-functionalised mesoporous SBA-15 silicas work well for the SPE of Pd (II) from digested samples (soil and road dust) with subsequent determination by slurry sampling ETAAS.…”
Section: Amines As Complexing Agents In Etaasmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure shows suitable analytical characteristics with a LOD of 0.64 ng L −1 , a linear calibration range of 2.5-100 ng L −1 , and RSD of 1.9% (n = 6; 10 ng L −1 ) with lifetimes above 800 cycles. 153 The successful application of primary and secondary amines (PSA) allows us to extract by SPE the available Pb (II) in soil samples by neutral salt extraction within the best pH range of 3.0-8.0. 154 Amine-and thiol-functionalised mesoporous SBA-15 silicas work well for the SPE of Pd (II) from digested samples (soil and road dust) with subsequent determination by slurry sampling ETAAS.…”
Section: Amines As Complexing Agents In Etaasmentioning
confidence: 99%
“…The procedure shows suitable analytical characteristics with a LOD of 0.64 ng L −1 , a linear calibration range of 2.5–100 ng L −1 , and RSD of 1.9% ( n = 6; 10 ng L −1 ) with lifetimes above 800 cycles. 153…”
Section: Amines As Organic Extractantsmentioning
confidence: 99%
“…The synthesized adsorbent can be reused up to 12 times, indicating decent stability. Minaberry Yanina Susana, et al, [ 92 ] reported an adsorbent based on magnetic material with ion imprinting (MII) for the separation of Cd(II) from tap water and osmosis water, and detection was carried out using GFAAS. The synthesized material is rich in amino (−NH 2 ) functional groups, and it can easily adsorb the Cd(II) (mild acidic nature).…”
Section: Recent Applications Of Mspe For Heavy Metal Analysis In Envi...mentioning
confidence: 99%
“…10–12 Compared to electrochemical methods, fluorescence spectroscopy, chromatography, mass spectrometry, and inductively coupled plasma atomic emission spectrometry, absorption spectroscopy has wide applications in in situ real-time monitoring due to its advantages of fast detection speed, simple operation, and easy maintenance. 13–19…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Compared to electrochemical methods, uorescence spectroscopy, chromatography, mass spectrometry, and inductively coupled plasma atomic emission spectrometry, absorption spectroscopy has wide applications in in situ real-time monitoring due to its advantages of fast detection speed, simple operation, and easy maintenance. [13][14][15][16][17][18][19] In the determination of absorption spectra, incident light passes through the sample and then the transmitted light signals are converted into electrical signals by the detector to form absorption spectra. 20,21 The detection limit and sensitivity of absorption spectra depend on the detector response to light, and the response signals decreasewith the decrease in concentration.…”
Section: Introductionmentioning
confidence: 99%